(untitled) (World Bulletin of Social Sciences, 2024)
This article explores the role of youth in the election process, focusing on both foreign and national experiences. Youth participation in elections is critical for shaping democratic governance and ensuring that the younger generation’s voice is heard in political decision-making. The study analyzes various approaches and methods used in different countries to engage young people in the electoral process, including policy initiatives, educational programs, and outreach campaigns. It also examines the challenges faced in increasing youth voter turnout and the impact of youth political engagement on election outcomes. A comparison between international practices and the national context highlights unique features of youth participation in elections, as well as opportunities for improving engagement strategies in the future.